# The differential equation obtained by eliminating A and B from $y = A\cos \omega t + B\sin \omega t$ is

$

(a){\text{ y'' + y' = 0}} \\

(b){\text{ y'' + }}{\omega ^2}{\text{y = 0}} \\

(c){\text{ y'' = }}{\omega ^2}{\text{y}} \\

(d){\text{ y'' + y = 0}} \\

$

Answer

Verified

363k+ views

Hint: In this question we have been given an equation and we need to obtain the differential equation that will be obtained by eliminating A and B. Now we have to eliminate two variables so we have to differentiate this equation twice. Use this concept to get the answer.

Complete step-by-step answer:

Given equation is

$y = A\cos \omega t + B\sin \omega t$…………………. (1)

Now differentiate this equation w.r.t. t then we have,

$\dfrac{{dy}}{{dt}} = y' = A\dfrac{d}{{dt}}\left( {\cos \omega t} \right) + B\dfrac{d}{{dt}}\left( {\sin \omega t} \right)$

Now apply the differentiation of cosine and sine we have,

$ \Rightarrow y' = A\left( { - \sin \omega t\dfrac{d}{{dt}}\left( {\omega t} \right)} \right) + B\left( {\cos \omega t\dfrac{d}{{dt}}\left( {\omega t} \right)} \right)$

And we all know differentiation of $\omega t$ w.r.t. t is $\omega $.

$ \Rightarrow y' = A\left( { - \omega \sin \omega t} \right) + B\left( {\omega \cos \omega t} \right)$

$ \Rightarrow y' = - A\omega \sin \omega t + B\omega \cos \omega t$

Now again differentiate this equation w.r.t. t we have,

$ \Rightarrow \dfrac{d}{{dt}}y' = y'' = - A\omega \left( {\dfrac{d}{{dt}}\sin \omega t} \right) + B\omega \left( {\dfrac{d}{{dt}}\cos \omega t} \right)$

Now again apply the differentiation of cosine and sine we have,

$ \Rightarrow y'' = - A\omega \left( {\cos \omega t\dfrac{d}{{dt}}\left( {\omega t} \right)} \right) + B\omega \left( { - \sin \omega t\dfrac{d}{{dt}}\left( {\omega t} \right)} \right)$

$ \Rightarrow y'' = - A\omega \left( {\omega \cos \omega t} \right) + B\omega \left( { - \omega \sin \omega t} \right)$

Now simplify this equation we have,

$ \Rightarrow y'' = - A{\omega ^2}\cos \omega t - B{\omega ^2}\sin \omega t$

$ \Rightarrow y'' = - {\omega ^2}\left( {A\cos \omega t + B\sin \omega t} \right)$

Now from equation (1) we have,

$ \Rightarrow y'' = - {\omega ^2}y$

$ \Rightarrow y'' + {\omega ^2}y = 0$

So, this is the required differential equation.

Hence option (b) is correct.

Note: Whenever we face such types of problems the key concept is to know that the total number of variables that has to be eliminated is the number of times we have to differentiate that given equation. Differentiation and simplification alongside will get you the required differential equation.

Complete step-by-step answer:

Given equation is

$y = A\cos \omega t + B\sin \omega t$…………………. (1)

Now differentiate this equation w.r.t. t then we have,

$\dfrac{{dy}}{{dt}} = y' = A\dfrac{d}{{dt}}\left( {\cos \omega t} \right) + B\dfrac{d}{{dt}}\left( {\sin \omega t} \right)$

Now apply the differentiation of cosine and sine we have,

$ \Rightarrow y' = A\left( { - \sin \omega t\dfrac{d}{{dt}}\left( {\omega t} \right)} \right) + B\left( {\cos \omega t\dfrac{d}{{dt}}\left( {\omega t} \right)} \right)$

And we all know differentiation of $\omega t$ w.r.t. t is $\omega $.

$ \Rightarrow y' = A\left( { - \omega \sin \omega t} \right) + B\left( {\omega \cos \omega t} \right)$

$ \Rightarrow y' = - A\omega \sin \omega t + B\omega \cos \omega t$

Now again differentiate this equation w.r.t. t we have,

$ \Rightarrow \dfrac{d}{{dt}}y' = y'' = - A\omega \left( {\dfrac{d}{{dt}}\sin \omega t} \right) + B\omega \left( {\dfrac{d}{{dt}}\cos \omega t} \right)$

Now again apply the differentiation of cosine and sine we have,

$ \Rightarrow y'' = - A\omega \left( {\cos \omega t\dfrac{d}{{dt}}\left( {\omega t} \right)} \right) + B\omega \left( { - \sin \omega t\dfrac{d}{{dt}}\left( {\omega t} \right)} \right)$

$ \Rightarrow y'' = - A\omega \left( {\omega \cos \omega t} \right) + B\omega \left( { - \omega \sin \omega t} \right)$

Now simplify this equation we have,

$ \Rightarrow y'' = - A{\omega ^2}\cos \omega t - B{\omega ^2}\sin \omega t$

$ \Rightarrow y'' = - {\omega ^2}\left( {A\cos \omega t + B\sin \omega t} \right)$

Now from equation (1) we have,

$ \Rightarrow y'' = - {\omega ^2}y$

$ \Rightarrow y'' + {\omega ^2}y = 0$

So, this is the required differential equation.

Hence option (b) is correct.

Note: Whenever we face such types of problems the key concept is to know that the total number of variables that has to be eliminated is the number of times we have to differentiate that given equation. Differentiation and simplification alongside will get you the required differential equation.

Last updated date: 27th Sep 2023

•

Total views: 363k

•

Views today: 8.63k

Recently Updated Pages

What is the Full Form of DNA and RNA

What are the Difference Between Acute and Chronic Disease

Difference Between Communicable and Non-Communicable

What is Nutrition Explain Diff Type of Nutrition ?

What is the Function of Digestive Enzymes

What is the Full Form of 1.DPT 2.DDT 3.BCG

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

The equation xxx + 2 is satisfied when x is equal to class 10 maths CBSE

Who had given the title of Mahatma to Gandhi Ji A Bal class 10 social science CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

How many millions make a billion class 6 maths CBSE

Find the value of the expression given below sin 30circ class 11 maths CBSE